Assessment of Body Composition From CT Images at the Level of the Third Lumbar Vertebra in Inflammatory Bowel Disease. Issue 9 (25th November 2020) - Bamba, Shigeki; Inatomi, Osamu; Takahashi, Kenichiro; Morita, Yasuhiro; Imai, Takayuki; Ohno, Masashi; Kurihara, Mika; Takebayashi, Katsushi; Kojima, Masatsugu; Iida, Hiroya; Tani, Masaji; Sasaki, Masaya
Abstract: Background: Although there are several reports of associations between body composition parameters and outcomes in patients with inflammatory bowel disease (IBD), it is not clear which muscle tissue parameters and/or adipose tissue parameters most strongly affect outcomes. Therefore, this study sought to determine the associations of such parameters determined at the level of the third lumbar vertebra (L3) on computed tomography (CT) images with outcomes in IBD patients. Methods: Subjects were IBD patients who were admitted to our hospital and underwent abdominal CT. The following parameters were assessed: skeletal muscle index, psoas muscle index, visceral adipose tissue/height index, visceral to subcutaneous adipose tissue area ratio, and intramuscular adipose tissue content. In this study, short- and long-term outcomes were defined as prolonged length of stay (≥30 days) and intestinal resection during the overall period of observation, respectively. Results: In total, 187 patients were enrolled, 99 with Crohn's disease and 88 with ulcerative colitis. For all IBD patients, multivariate logistic regression analysis revealed that low albumin level and low psoas muscle index on admission were associated with prolonged length of stay. Multivariate Cox regression analysis revealed that male sex, Crohn's disease (not ulcerative colitis), low psoas muscle index, and high visceral to subcutaneous adipose tissue area ratio were associated with intestinal resection. Conclusions: This study revealed that muscle volume is associated with the short-term outcome of prolonged length of stay, whereas muscle volume and visceral adipose tissue volume (relative to subcutaneous adipose tissue volume) are associated with the long-term outcome of intestinal resection.